2017
DOI: 10.1293/tox.2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium exposure on Iberian ribbed newt (<i>Pleurodeles waltl</i>) testes

Abstract: To characterize the histomorphologic effects of cadmium on adult newt testes, male Iberian ribbed newts (6 months post-hatching) were intraperitoneally exposed to a single dose of 50 mg/kg of cadmium, with histologic analysis of the testes at 24, 48, 72, and 96 h. Beginning 24 h after cadmium exposure, apoptosis of spermatogonia and spermatocytes was observed, and congestion was observed in the interstitial vessels of the testes. Throughout the experimental period, the rates of pyknotic cells and TUNEL and cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Cadmium-induced testis showed increased activity of caspase 3 and 9, which increases the number of morphological signs of apoptosis, including chromatin decondensation and marginalization in primary spermatocytes, loss of the nuclear envelope in the spermatogonium, disruption of mitochondrial membrane potential (MMP), degradation of cytoplasmic organelles, and DNA distribution [ 102 ]. The testicles of rats [ 103 ], fish [ 104 ], and lizard [ 105 ] all showed evidence of cadmium-induced spermatogonia and spermatocyte apoptosis. The concentration-dependent effect of cadmium on human embryonic germ cell apoptosis was revealed by immune signaling detection of caspase 3 in testicular tissue [ 106 ].…”
Section: Effect Of Cadmium On Spermatogenesismentioning
confidence: 99%
“…Cadmium-induced testis showed increased activity of caspase 3 and 9, which increases the number of morphological signs of apoptosis, including chromatin decondensation and marginalization in primary spermatocytes, loss of the nuclear envelope in the spermatogonium, disruption of mitochondrial membrane potential (MMP), degradation of cytoplasmic organelles, and DNA distribution [ 102 ]. The testicles of rats [ 103 ], fish [ 104 ], and lizard [ 105 ] all showed evidence of cadmium-induced spermatogonia and spermatocyte apoptosis. The concentration-dependent effect of cadmium on human embryonic germ cell apoptosis was revealed by immune signaling detection of caspase 3 in testicular tissue [ 106 ].…”
Section: Effect Of Cadmium On Spermatogenesismentioning
confidence: 99%
“…Various morphological characteristics of apoptosis, eg, chromatin condensation and marginalization in primary spermatocytes, degeneration of cytoplasmic organelles, disappeared nuclear envelope in spermatogonium, and fragmentation of DNA were observed in Cd‐intoxicated testes of freshwater crab ( Sinopotamon henanense ), along with increased activities of caspase‐3 and ‐9 in a concentration‐dependent manner (Wang et al, 2011). Other morphological and ultrastructural studies have also reported Cd‐induced apoptosis of spermatogonia and spermatocytes in rodents (Boujelben, Abdennabi, Guermazi, & Elfeki, 2018; Niknafs et al, 2015), fish (Hirako, Takeoka, Furukawa, & Sugiyama, 2017) and newt (Hirako et al, 2017) testis, respectively. A concentration‐dependent effect of Cd on apoptosis of human fetal germ cells was illustrated by immunohistochemical detection of caspase‐3 in testicular tissue under in vitro conditions (Angenard et al, 2010).…”
Section: Cadmium‐mediated Toxicity In Testesmentioning
confidence: 90%
“…This includes chromatin decondensation and marginalization in primary spermatocytes, loss of the nuclear envelope in spermatogonia, alterations in DNA distribution, degradation of cytoplasmic organelles, and disruption of mitochondrial membrane potential [35]. Apoptosis induced by cadmium has been observed in the testes of various mammalian species [36][37][38]. In humans, the concentration-dependent impact of cadmium on the death of embryonic germ cells has been demonstrated through the detection of caspase 3 enzyme activity in testicular tissue [39].…”
Section: Revi Ew Art I Cl Ementioning
confidence: 99%